2019
DOI: 10.1002/cpt.1553
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen‐Containing Oral Contraceptives Are Associated With Polycystic Liver Disease Severity in Premenopausal Patients

Abstract: The association between estrogen‐containing oral contraceptives and history of pregnancies with disease severity in women with polycystic liver disease (PLD) is unclear. We performed a cross‐sectional cohort study to assess this association by selecting female patients with PLD of which imaging was available prior to any liver volume‐reducing therapy. Patients received a questionnaire to collect detailed information on estrogen use and pregnancies. Preplanned subgroup analyses were performed on premenopausal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 26 publications
(42 reference statements)
0
50
0
Order By: Relevance
“…Differences in disease severity between males and females could be caused by genetic differences, epigenetic differences and by differences in hormone levels. It is known that estrogen supplementation stimulates growth 18,19 . In addition, recent data suggest that liver growth does not follow a linear pattern with age, as was previously thought, but liver volumes spontaneously decrease after menopause in female patients 20 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Differences in disease severity between males and females could be caused by genetic differences, epigenetic differences and by differences in hormone levels. It is known that estrogen supplementation stimulates growth 18,19 . In addition, recent data suggest that liver growth does not follow a linear pattern with age, as was previously thought, but liver volumes spontaneously decrease after menopause in female patients 20 .…”
Section: Introductionmentioning
confidence: 86%
“…Sixty‐four articles were retrieved. All titles and relevant abstracts were read and 9 articles were selected for review 18,19,21–27 . The other 53 were not relevant for this review, see Supplementary Table for specific reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal replacement therapy with conjugated estrogens in 19 post-menopausal ADPKD patients was associated with an increase in TLV, compared to a volume reduction in controls [56]. In addition, a recent large cross-sectional cohort study showed that every 10 years of oral contraceptive use in premenopausal women was correlated with a 15.5% higher heightadjusted TLV compared to unexposed women [57]. These findings led to the clinical advice to discourage the use of exogenous estrogens in female PLD patients.…”
Section: Estrogen and Progestogenmentioning
confidence: 99%
“…We believe that the female hormone pathway is the most promising future therapeutic target due to several reasons: 1. the majority of PLD patients are female [1]; 2. female patients express a more severe phenotype compared to males [13,56]; 3. growth of polycystic liver declines after menopause [3,53]; 4. exogenous estrogens are a risk factor for hepatic cyst growth in PLD [57]; and 5. postmenopausal hormone administration increases cyst volume [56]. Altogether, these arguments suggest that inducing a post-menopausal status in female PLD patients, for example with GnRH agonists, would be a logical next step.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Although fertility control agents, such as oestrogen and triptolide, can cause temporary infertility in animals, they can be toxic (Kejuan et al 2007;Lipschutz et al 1966;Maier & Herman 2001;van Aerts et al 2019;Xu et al 2019;Yuan et al 2019) and can cause death at higher dosages (Lehmann et al 1989;Zhang et al 2015;Zhang 2015). Therefore, it is important to estimate the toxicity in animals prior to using fertility control agents (Ettlin & Prentice 2002;Gao & Short 1993;Ratti et al 2015;Turner et al 2011;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%